2021
DOI: 10.3390/ijms222111925
|View full text |Cite
|
Sign up to set email alerts
|

Central Carbon Metabolism, Sodium-Motive Electron Transfer, and Ammonium Formation by the Vaginal Pathogen Prevotella bivia

Abstract: Replacement of the Lactobacillus dominated vaginal microbiome by a mixed bacterial population including Prevotella bivia is associated with bacterial vaginosis (BV). To understand the impact of P. bivia on this microbiome, its growth requirements and mode of energy production were studied. Anoxic growth with glucose depended on CO2 and resulted in succinate formation, indicating phosphoenolpyruvate carboxylation and fumarate reduction as critical steps. The reductive branch of fermentation relied on two highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Prevotella has been the model genus in two of the works published in this Special Issue. Schleicher and coworkers observed that the vaginal microbiome dominated by lactobacillus is replaced by a mixed bacterial population including Prevotella bivia [4]. P. bivia is associated with bacterial vaginosis, and consequently connected with a variety of health abnormalities, such as preterm births, increased susceptibility to sexually transmitted pathogens, or a higher risk of pelvic inflammatory disease.…”
mentioning
confidence: 99%
“…Prevotella has been the model genus in two of the works published in this Special Issue. Schleicher and coworkers observed that the vaginal microbiome dominated by lactobacillus is replaced by a mixed bacterial population including Prevotella bivia [4]. P. bivia is associated with bacterial vaginosis, and consequently connected with a variety of health abnormalities, such as preterm births, increased susceptibility to sexually transmitted pathogens, or a higher risk of pelvic inflammatory disease.…”
mentioning
confidence: 99%